The Influence of Social Media Marketing, Perceived Quality, and Brand Advocacy on Buying Interest Wardah Brand Cosmetics in East Java UPN "Veteran" Students - Rosyidah, If'idatur; Purwanto, Sugeng (Formosa Journal of Multidisciplinary Research, 2024)
Technological innovations are currently undergoing tremendous growth. The large number of internet users and social media is a sign of technological progress. In addition, the beauty business is also seeing fast expansion. Therefore, many brands from this industry are renewing to attract people's buying interest. This study aims to determine the influence of Social Media Marketing, Perceived Quality, and Brand Advocacy on Wardah Cosmetics Buying interest in UPN "Veteran" East Java Students. The data collection method used was through the distribution of questionnaires. A sampling of this study uses a purposive sampling technique with 100 respondents. Data analysis technique using SmartPLS ver 4.1. The results showed that Social Media Marketing, Perceived Quality, and Brand Advocacy have a positive and cynical influence on Buying interest.